Stock Market Reaction to the Announcement of Law Number 7 of 2021 Regarding Harmonization of Tax Regulations (E-Jurnal Akuntansi, 2024)
The announcement of the implementation of government policy, specifically tax reformation policy, indicates a shift in tax management and the amount of tax obligations that must be borne. The purpose of this study is to demonstrate empirically that the capital market reacted to the announcement of the implementation of Law Number 7 of 2021 concerning the harmonization of tax regulations. This research is an event study with an event window of 7 trading days. This research was conducted at the Indonesia Stock Exchange, with a total population of 728 companies. Samples were taken using a proportioned stratified random sampling technique of 258 companies. The analysis technique used is the one-sample t-test on the cumulative abnormal return (CAR). The test results show that there is no market reaction as seen from the absence of significant abnormal returns around the event date.
Keywords: Event Study; Abnormal Return; Harmonization of Tax Regulation; Stock Market Reaction